Reconstitution of autophagosome nucleation defines Atg9 vesicles as seeds for membrane formation - Sawa-Makarska, Justyna (Science, 2020)
Autophagosomes form de novo in a manner that is incompletely understood. Particularly enigmatic are Atg9 containing vesicles that are required for autophagy machinery assembly but do not supply the bulk of the autophagosomal membrane. Here we reconstituted autophagosome nucleation using recombinant components from yeast. We found that Atg9 proteoliposomes first recruited the phosphatidylinositol 3-phosphate kinase complex, followed by Atg21, the Atg2-Atg18 lipid transfer complex and the E3-like Atg12–Atg5-Atg16 complex, which promoted Atg8 lipidation. Furthermore, we found that Atg2 could transfer lipids for Atg8 lipidation. In selective autophagy these reactions could potentially be coupled to the cargo via the Atg19-Atg11-Atg9 interactions. We thus propose that Atg9 vesicles form seeds that establish membrane contact sites to initiate lipid transfer from compartments such as the endoplasmic reticulum.